HISTORICAL GLIMPSE FROM THE INTERNATIONAL EXPERIENCE OF KNOWLEDGE ASSESSMENT - VOSKANYAN, SHOGHIK; HOVHANNISYAN, EDITA (Main Issues Of Pedagogy And Psychology, 2014)
As a sphere of social practice education is a link between experience gathered by humanity, knowledge about nature, society and human beings and the possibilities of preserving and transfering them. Being a sphere of personal activity, education develops human intellect, forms moral, esthetical, national and general values, and engenders the desire to reach personal and social perfection. Education is a multiform process of borrowing and transferring from generation to generation scientific information, acquired social and professional experience, as well as assimilated social culture. One of the indispensable criteria of education is knowledge; those are facts and phenomena of objective reality assimilated and memorized by human beings. Knowledge is the entity of human ideas and their logical union; it expresses the theoretical assimilation of one or another discipline by the pupil. Knowledge is a system of values, so it must be estimated. In diverse periods and diverse countries estimation of knowledge was made by diverse methods, taking into consideration notions about the knowledge level existing at that time.